2023
DOI: 10.53855/bjt.v26i1.500_eng
|View full text |Cite
|
Sign up to set email alerts
|

The Halifax flow Crossmatch Protocol Results According to the HLA Class and MFI of the DSA

Abstract: Introduction: The main strategy to reduce the immunogenicity of transplanted grafts is to seek maximum compatibility between alloantigens in the donor-recipient pair. It is understood that the virtual crossmatch (VXM) can be a good tool in the evaluation of the donor / recipient pair and that a broader application of these protocols will improve the pre-transplant immunological risk assessment. The aim of this study was to correlate the physical flow crossmatches results, looking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Additionally, research has demonstrated that patients transplanted with a negative FCXM result, but a positive VXM results are at an elevated risk of AMR and experience a shorter graft survival. [27–35]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, research has demonstrated that patients transplanted with a negative FCXM result, but a positive VXM results are at an elevated risk of AMR and experience a shorter graft survival. [27–35]…”
Section: Introductionmentioning
confidence: 99%
“…A weak antibody that does not reach a positive FCXM: In general, studies have shown that a positive FCXM can be obtained with MFI ≥ 2500. [31,50] However, it is worth noting that the success of any physical crossmatching test relies on the quality of the donor cells, and it is known that HLA expression can vary depending on whether the donor is living or deceased, as well as the source of the cells, whether from peripheral blood, spleen, or lymph node. Certain medications, such as statins and steroids, can decrease HLA expression.…”
Section: Introductionmentioning
confidence: 99%